A new method for the preparation of piperidin-4-ones. (18th June 2021) - Hoffelner, Michael; Seebacher, Werner; Hassan, Usama; Leitner, Andreas; Weis, Robert; Saf, Robert
Abstract: We describe a new reduction process for the efficient preparation of various, especially 2-substituted, piperidin-4-ones which are not accessible by other reaction pathways until now. Tetrahydropyridinylidene salts (THPS) with differing substitution pattern are the educts of this reaction. These compounds are available by mainly two different reaction sequences and they can be further modified by insertion of various substituents before the targeted piperidin-4-ones are obtained. Graphical abstract: Image 1 Highlights: Piperidin-4-ones are important intermediates for the syntheses of 4-amino-piperidine therapeutic compounds. New method for the preparation of substituted piperidin-4-ones from tetrahydropyridinylidene salts. 2-Substituted piperidin-4-ones are rarely available. Preparation of 2, 2-dimethyl fentanyl as an example for a 2-substituted drug.